2018
DOI: 10.1080/2162402x.2017.1408749
|View full text |Cite
|
Sign up to set email alerts
|

Virus-like particle display of HER2 induces potent anti-cancer responses

Abstract: Overexpression of human epidermal growth factor receptor-2 (HER2) occurs in 20–30% of invasive breast cancers. Monoclonal antibody therapy is effective in treating HER2-driven mammary carcinomas, but its utility is limited by high costs, side effects and development of resistance. Active vaccination may represent a safer, more effective and cheaper alternative, although the induction of strong and durable autoantibody responses is hampered by immune-tolerogenic mechanisms. Using a novel virus-like particle (VL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
102
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(102 citation statements)
references
References 111 publications
0
102
0
Order By: Relevance
“…The results revealed that the vaccine significantly hampered the growth of the established tumors and prevented pulmonary metastases (Bolli et al, 2018). Palladini et al (2018) have designed a unique VLP-based vaccine allowing a directional and high-density display of the full extracellular domain of HER-2 (subdomain I-IV) on the surface of AP205-VLPs. The developed vaccine is based on a SpyTag/SpyCatcher conjugation system where HER-2 antigen was genetically fused to the SpyCatcher sequence which is attached to the surface of AP205-VLPs expressing the "SpyTag" (Figure 6b).…”
Section: Vlp-based Vaccines Against Breast Cancermentioning
confidence: 99%
“…The results revealed that the vaccine significantly hampered the growth of the established tumors and prevented pulmonary metastases (Bolli et al, 2018). Palladini et al (2018) have designed a unique VLP-based vaccine allowing a directional and high-density display of the full extracellular domain of HER-2 (subdomain I-IV) on the surface of AP205-VLPs. The developed vaccine is based on a SpyTag/SpyCatcher conjugation system where HER-2 antigen was genetically fused to the SpyCatcher sequence which is attached to the surface of AP205-VLPs expressing the "SpyTag" (Figure 6b).…”
Section: Vlp-based Vaccines Against Breast Cancermentioning
confidence: 99%
“…Vaccines presenting antigens on Virus-Like Particles (VLP) have been shown to induce high tittered, long lasting functional IgG responses in humans [29,30] and can drive immune responses even to weakly immunogenic or self-antgens [31,32]. We, and others, have recently developed a technique that allows effective coupling of complex proteins to pre-formed VLP and demonstrated that the IgG response to the proteins coupled is potent, functional, and durable even with self-antigens [31,33,34]. Here, VLP-CIDRα1.4 vaccines adjuvanted with aluminum hydroxide elicited stronger immune responses than a similar soluble CIDRα1 vaccine in Freund's incomplete adjuvant, and antibodies reactive and functionally inhibitory across group A CIDRα1 variants was elicited from immunization with a single CIDRα1 antigen variant.…”
mentioning
confidence: 99%
“…This system is already utilized to design different types of vaccines, including the vaccines against tuberculosis and malaria [84,85]. A recent report has demonstrated that it was successfully used to develop a vaccine against breast cancer [86]. This work is remarkable due to the fact that the high density of the HER2 antigen (human epidermal factor receptor 2) synthesized in the cultured Drosophila melanogaster cells could be obtained on the AP204 VLP surface [32].…”
Section: Recombinant Vlps For Presentation Of Foreign Antigenic Determentioning
confidence: 99%
“…This work is remarkable due to the fact that the high density of the HER2 antigen (human epidermal factor receptor 2) synthesized in the cultured Drosophila melanogaster cells could be obtained on the AP204 VLP surface [32]. The obtained particles induced a strong immune response to the antigen in the patients, which rendered it possible to overcome the immune tolerance to HER2 known for patients with the HER2-dependent breast cancer [85,86].…”
Section: Recombinant Vlps For Presentation Of Foreign Antigenic Determentioning
confidence: 99%
See 1 more Smart Citation